2018
DOI: 10.21037/jtd.2018.02.66
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and muscle dysfunction in chronic respiratory diseases: stable phase versus acute exacerbations

Abstract: Nutritional abnormalities are frequent in different chronic respiratory diseases such as chronic obstructive pulmonary disease (COPD), bronchiectasis, cystic fibrosis (CF), interstitial fibrosis and lung cancer, having important clinical consequences. However, nutritional abnormalities often remained underdiagnosed due to the relative lack of awareness of health professionals. Therefore, systematic anthropometry or even better, assessment of body composition, should be performed in all patients with chronic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 286 publications
(330 reference statements)
1
54
0
7
Order By: Relevance
“…Malnutrition is common in chronic respiratory diseases, including COPD, and may be underdiagnosed because of a lack of awareness among healthcare professionals . Nutrition screening should occur for all COPD patients with assessment as indicated, especially in those with more‐severe disease and during exacerbations.…”
Section: Resultsmentioning
confidence: 99%
“…Malnutrition is common in chronic respiratory diseases, including COPD, and may be underdiagnosed because of a lack of awareness among healthcare professionals . Nutrition screening should occur for all COPD patients with assessment as indicated, especially in those with more‐severe disease and during exacerbations.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that nutritional status may be difficult to assess based on SGA and BMI parameters alone. In patients with advanced IPF awaiting lung transplantation, severe depletion of lean body mass, a circumstance generally associated with muscle dysfunction [41], was observed in as much as 56% of patients [48]. Although combined losses of body weight and lean mass were seen in some patients, lean body mass depletion was not always associated with low body weight as it was potentially masked by a relative abundance in fat mass.…”
Section: Discussionmentioning
confidence: 97%
“…A reduction in physical activity seen in ILD patients is multifactorial, and may initially result from ventilatory limitation, as well as respiratory and psychological symptoms (cough, dyspnoea, anxiety and depression) which lead to exercise avoidance. This subsequently results in conditioning of different body components such as the cardiovascular system and limb muscles and bones, further limiting functional capacity [41]. Fortunately, the impairment in muscle function appears to be partially reversible with training [42].…”
Section: Discussionmentioning
confidence: 99%
“…Muscle mass loss and dysfunction (sarcopenia) are characteristic features of patients with chronic respiratory and cardiac conditions and also in cancer. Several studies have shown that for the same degree of airway obstruction in patients with chronic obstructive pulmonary disease (COPD), poor muscle mass, and weakness of the quadriceps negatively influenced their quality of life and prognosis (Gea & Martínez-Llorens, 2018;Gea, Pascual, et al, 2018;Gea, Sancho-Muñoz, & Chalela, 2018;Gosselink, Troosters, & Decramer, 2000;Marquis et al, 2002;Seymour et al, 2010;Shrikrishna et al, 2012;Swallow et al, 2007). In patients with lung cancer (LC), muscle wasting and cachexia also reduced their quality of life and survival (Evans et al, 2008;Fearon et al, 2011).…”
Section: Introductionmentioning
confidence: 99%